Motivasi, Pemahaman Profesi Guru, Dan Pengaruhnya Terhadap Pemilihan Program Studi Di Lingkungan Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pancasakti Tegal (Studi Kasus Mahasiswa Angkatan Ta 2015-2016) - Sri Wardhani; Yulia Nur Ekawati; Anin Eka Sulistyawati (Cakrawala: Jurnal Pendidikan, 2017)
A profession of teacher cannot be forced, since it comes from their self-awareness and sincerity. Teacher Training Institute (LPTK) as an institute which produces teachers has an important role in producing professional teachers. Based on the background above, this research tries to find out whether there is a significant effect between students’ motivation and choosing on study program at Faculty of Teacher Training and Education in Pancasakti University Tegal and whether there is significant relationship between their understanding on teacher profession in choosing study program at Faculty of Teacher Training and Education in Pancasakti University Tegal. This research is a case study which concerns on finding determination factors in influencing students in choosing their study program in Faculty of Teacher Training and Education. The instrument to collect the data is questionnaire. The result of questionnaire which has been completed by students of seven study programs in the Faculty of Teacher Training and Education in Pancasakti University Tegal is calculated and analyzed by statistic calculation using SPSS program. This research result shows there is no significant effect between students’ motivation in choosing study program at Faculty of Teacher Training and Education in Pancasakti University Tegal as well as there is also no significant relationship between students’ understanding on teacher profession in choosing study program at Faculty of Teacher Training and Education in Pancasakti University Tegal